Social networking of innovative farmers through WhatsApp messenger for learning exchange: A study of content sharing - NAIN, MANJEET SINGH; SINGH, RASHMI; MISHRA, J R (The Indian Journal of Agricultural Sciences, 2019)
Farm Innovators are regularly exchanging information and their experiences using WhatsApp messenger on their mobile phones. Most of the content shared was knowledge intensive with a mix of personal farming experiences. As Social constructivist learning theory seeks to improve socialinteractions to construct and share knowledge and the social networking through WhatsApp has proved to be potential to construct knowledge. Learning being the outcome of interactions between cognitive and psychological and the WhatsApp being the potential source for socialization and internalization promoted the creation ofsocial wealth in the form of discussion forums of Innovative farmers for learning exchange. The extension mechanism for purposeful farmer to farmer learning exchange has been created which in turn is a step towards innovative farmer led extension delivery mechanism. The potential of not only WhatsApp but other social media need to be exploited to bring location specific and commodity oriented transformative changes in the agriculture extension delivery system. The experimentation with innovative farmers is not only helping in scaling the farmers’ innovations but also institutional innovations at large. As all human resources (labour, management, innovation, creativity) are products of social relationships, no one can reach maturity without the help of personally caring people, including their families, friends, neighbors, and communities. Farms and agricultural enterprises also depend on the ability of people to work together toward the common goal of ecological, social, and economic sustainability through social networks.